Anisotropic magnetic-field-induced phase transition in MnAs nanoribbons - Fernandez Baldis, Federico Jose (2015)
MnAs thin films present a phase coexistence of regularly arranged ferromagnetic (alfa) and paramagnetic (beta) stripes below the Curie temperature when grown onto GaAs(100) substrates. In this letter, we report the observation of a magneto-structural phase transition induced by magnetic field on MnAs nanoribbons below the Curie temperature. A transformation of high-resistance paramagnetic regions into low-resistance ferromagnetic ones is observed above temperature-dependentcritical magnetic fields. The phenomenon is hysteretic, highly anisotropic, and size dependent and could be the origin of the high magneto-resistance effect observed at temperatures close to room temperature in these systems.